Bound by debt: Nutmeg trees and changing relations between farmers and agents in a Moluccan agroforestry systems - Messalina Lovenia Salampessy; Indra Gumay Febryano; Dini Zulfiani (Forest and Society, 2017)
Agroforestry is a land management system long practiced by communities in the Moluccas. The practice is commonly known as "Dusung", where one cash crop in particular, nutmeg, is interspersed throughout farmer groves. Farmers have faced a number of challenges in recent years, especially concerning a system of debt bondage inflicting undue losses upon them. This study aims to explain the involvement of farmers within the debt bondage system, otherwise known as the tree mortgage system. We utilize a case study methodology, whereby data were collected through interviews and participant observation and results analyzed using principal agent theory. Findings highlight that nutmeg farmers, what we call the Principal, incur high risks when debt bondage is applied by an Agent that has the increasing ability to deny and change the terms of an agreement. This occurs when Agents exploit information unavailable to farmers about nutmeg marketing prospects, which weakens farmer negotiating positions. Improving institutional support for contracts in the tree mortgage system could help to ensure a more equitable arrangement, improving the terms for nutmeg farmers, meanwhile also encouraging the continued preservation of the dusung system, which has long helped to manage forest resources sustainably.